ACTIVE TECTONICS IN THE HELLENIC VOLCANIC ARC: THE KOLUMBO SUBMARINE VOLCANIC ZONE - Sakellariou, D.; Sigurdsson, H.; Alexandri, M.; Carey, S.; Rousakis, G.; Nomikou, P.; Georgiou, P.; Ballas, D. (Bulletin of the Geological Society of Greece, 2010)
This paper studies the rupture system of the Anydhros Basin, northeast of Thera island, and its relationship to the submarine volcanic activity along the Kolumbo line. Anydhros Basin is a N45o E trending elongate basin bounded by the Ios-Fault-Zone (IFZ) towards NW and by the AnydhrosFault-Zone (AFZ) towards SE. The AFZ continues southwestwards, crosscutting Thera Island. Swath bathymetry and seismic profiling data indicate that the Anydhros basin sedimentary infill is fractured by vertical, predominantly strike-slip faults, parallel to which the volcanic cones are aligned. We propose that the “KameniKolumbo Line” is an active, 40km-long, strike-slip fault zone. The KameniKolumbo strike slip runs through the volcanoes of Nea Kameni and Kolumbo and controls the spatial distribution of the volcanic cones along the axis of Anyhdros basin.